Inhibition of G Protein-Coupled P2Y2 Receptor Induced Analgesia in a Rat Model of Trigeminal Neuropathic Pain. (18th March 2014) - Li, Na; Lu, Zhan-Ying; Yu, Li-Hua; Burnstock, Geoffrey; Deng, Xiao-Ming; Ma, Bei
Backgrouds: ATP and P2X receptors play important roles in the modulation of trigeminal neuropathic pain, while the role of G protein-coupled P2Y2 receptors and the underlying mechanisms are less clear. The threshold and frequency of action potentials, fast inactivating transient K+ channels (IA ) are important regulators of membrane excitability in sensory neurons because of its vital role in the control of the spike onset. In this study, pain behavior tests, QT-RT-PCR, immunohistochemical staining, and patch-clamp recording, were used to investigate the role of P2Y2 receptors in pain behaviour. Results: In control rats: 1) UTP, an agonist of P2Y2 /P2Y4 receptors, caused a significant decrease in the mean threshold intensities for evoking action potentials and a striking increase in the mean number of spikes evoked by TG neurons. 2) UTP significantly inhibited IA and the expression of Kv1.4, Kv3.4 and Kv4.2 subunits in TG neurons, which could be reversed by the P2 receptor antagonist suramin and the ERK antagonist U0126. In ION-CCI (chronic constriction injury of infraorbital nerve) rats: 1) mRNA levels of Kv1.4, Kv3.4 and Kv4.2 subunits were significantly decreased, while the protein level of phosphorylated ERK was significantly increased. 2) When blocking P2Y2 receptors by suramin or injection of P2Y2R antisense oligodeoxynucleotides both led to a time- and dose-dependent reverse of allodynia in ION-CCI rats. 3) Injection of P2Y2 receptor antisense oligodeoxynucleotides induced a pronounced decrease in phosphorylated ERK expression and a significant increase in Kv1.4, Kv3.4 and Kv4.2 subunit expression in trigeminal ganglia. Conclusions: Our data suggest that inhibition of P2Y2 receptors leads to down-regulation of ERK-mediated phosphorylation and increase of the expression of IA –related Kv channels in trigeminal ganglion neurons, which might contribute to the clinical treatment of trigeminal neuropathic pain.